Design and kinematic analysis of a 3-RRR spherical parallel manipulator reconfigured with four–bar linkages. (April 2019) - Wu, Guanglei; Bai, Shaoping
Highlights: 3-RRR spherical parallel manipulator of co-axis input featuring a full-circle twist movement is redesigned with reconfigurability. Reconfiguration approach can be readily realized by utilizing a simple four-bar linkage. The variations of the manipulator performance can be achieved by adjusting one geometric parameter to ease the control. Some new features are revealed for the reconfigured SPM. The new design can be used for applications such as flight simulator or robotic joints. Abstract: In this paper, the 3-RRR spherical parallel manipulator (SPM) of co-axis input is redesigned with reconfigurability. By utilizing a simple four-bar linkage, the SPM is able to change virtually the dimensions of driving links. The new design allows the SPM reconfigurable for investigation of the influence of the link dimensions on the kinematic and dynamic performance of the SPM. Moreover, the new design can be used directly for the applications such as flight simulator. In this paper, the workspace, dexterity and singularity of the new design are investigated, considering the effect of an adjustable link dimension onto the manipulator performance. The relationship between the varying link dimension in a prescribed range and the operational workspace is studied, with some new results on workspace and dexterity of the SPM revealed.